Exploring the Value of Educational Accessibility and Learning through Virtual Worlds - Irene Wahba; James Braman; Cody Fountain (European Alliance for Innovation (EAI), 2016)
Virtual worlds allow for an immersive 3D experience with rich interactive content and learning potential for students. Through this technology, educators have abundant creative power to design and facilitate meaningful learning experiences. Even though online games and virtual worlds have been around for many years, their use in education has often been experimental or narrowed to a particular course topic. With the rapid changes in technology and advancements with computer interaction, virtual worlds are increasingly being used in numerous ways to improve learning and student-teacher interaction. In this editorial our aim is to briefly discuss virtual worlds in the context of education, with the focus of educational accessibility for students with disabilities.